Pengaruh Fundamental Saham, Tingkat Efektifitas Manajemen Terhadap Harga Saham dan Perataan Laba - Gusti Arya Wilwatikta Bayu; A.A.N. Eddy Supriyadinata Gorda (Universitas Pendidikan Nasional, 2016)
Associated with investments made the main purpose of investors are generallyfocused on profits or income so often found many managers intentionally reduce fluctuationsin reported earnings in order to achieve the desired level of profit. For the company performincome smoothing, which is one form of earnings management. As well as earningsmanagement, the concept of income smoothing found by agency theory, which assumed theprincipal (owner) and agent (management) have the same interests to maximize the utility ofeach of the information held, giving rise to a conflict of interest that is the asymmetry ofinformation , The research data from the Indonesia Stock Exchange service industry subsectorsproperty and real estate. Hypothesis testing results show that the PER positive andsignificant effect on stock prices, the level of PBV significant effect on stock prices, NPM hasa negative impact and no significant effect on the company's financial performance, ROIpositive and significant impact on stock prices, PER not significant effect on the index excel,PBV not significant effect on the index excel, NPM no significant effect on the index excel,ROI significant positive effect on excel index, stock price index significant positive effect onexcel.Keyword: PER, PBV, NPM, ROI, same price, income smoothing